Rancang Bangun Sistem Informasi Akademik Berbasis Web: Studi Kasus : SMP Negeri 2 Wewewa Utara - Ngongo, Agustina; Yulius Nahak Tetik; Mitra Permata Ayu (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2026)
The advancement of information technology today has provided great benefits in the world of education. The construction of computer-based academic information system websites is part of the use of information technology. With information technology, it is possible for academic databases to be processed quickly and easily, so that in the presentation of the required academic information reports can be obtained precisely, quickly, and efficiently. SMP Negeri 2 Wewewa Utara already has sufficient information technology infrastructure, but it has not been used optimally in academic management. The school already has a computer lab and internet access, but academic data management is still carried out manually using a ledger and Microsoft Excel application. To address issues such as unintegrated student data, complex and time-consuming grade management processes, delivering academic information, and monitoring student learning progress, an academic information system is needed. The purpose of developing this system is to solve the problems contained in the previous system by creating an academic information system at SMP N 2 Wewewa Utara. With the implementation of the new system at SMP N 2 Wewewa Utara, the knowledge and skills of employees, teachers, and principals in the field of web-based academic information systems can be improved. In the development of the academic information system that will be included in the system, it includes information about students, subjects, student classes, classrooms, teachers, homeroom teachers, and student score reports. The software used is DBMS (Database Management System), while the data storage medium is MySQL and PHP as a Programming Language.